Genetic variability, correlated response and path analysis of yield and yield contributing traits of spring wheat (Journal of the Bangladesh Agricultural University, 2010)
Twenty spring wheat varieties were studied to find out genetic variability and genetic association for grain yield and its component characters. Both genotypic and phenotypic variances were highly significant in all the traits with little higher phenotypic variations as usual. Similarly, the low differences between the phenotypic and genotypic coefficients of variations indicated low environmental influences on the expression of these characters. High heritability coupled with high genetic advance were obtained with plant height, grains per spike, 100-grain weight, harvest index and grain yield. Genotypic correlation coefficients were higher than the corresponding phenotypic correlation coefficients in most of the traits. Spikes per plant, grains per spike, spike length, 100-grain weight and harvest index were the most important characters which possessed positive association with grain yield. Path coefficient analysis revealed that among the different yield contributing characters spike per plant, grains per spike, 100-grain weight and harvest index influenced grain yield per plant directly. The direct effects of these characters on grain yield were positive and considerably high. Moreover, harvest index, days to maturity and spikes per plant had positive and higher indirect effect on grain yield through grains per spike. Thus selection for yield in spring wheat through these characters would be effective. Keywords: Variability; Selection indices; WheatDOI: 10.3329/jbau.v6i2.4815 J. Bangladesh Agril. Univ. 6(2): 227-234, 2008